Scent of a Killer: Microbial Volatilome and Its Role in the Biological Control of Plant Pathogens - Tilocca, Bruno; Cao, Aocheng; Migheli, Quirico (Frontiers in Microbiology, 2020)
The use of synthetic fungicides represents the most common strategy to control plant pathogens. Excessive and/or long-term distribution of chemicals is responsible for increased levels of environmental pollution, as well as adverse health consequence to humans and animals. These issues are deeply influencing public perception, as reflected by the increasing demand for safer and eco-friendly agricultural commodities and their by-products. A steadily increasing number of research efforts is now devoted to explore the use of safer and innovative approaches to control plant pathogens. The use of microorganisms as biological control agents (BCAs) represents one of the most durable and promising strategies. Among the panoply of microbial mechanisms exerted by BCAs, the production of volatile organic compounds (VOCs) represents an intriguing issue, mostly exploitable in circumstances where a direct contact between the pathogen and its antagonist is not practicable. VOCs are potentially produced by all living microorganisms, and may be active in the biocontrol of phytopathogenic oomycetes, fungi, and bacteria by means of antimicrobial activity and/or other cross-talk interactions. Their biological effects, the reduced residuals in the environment and on agricultural commodities, and the ease of application in different agricultural systems make the use of VOCs a promising and sustainable approach to replace synthetic fungicides in the control of plant pathogens. In this review, we focus on VOCs produced by bacteria and fungi and on their role in the cross-talk existing between the plant pathogens and their host. Biologic systemic effect of the microbial volatile blends on both pathogen and host plant cells is also briefly reviewed.